Microbial Pattern and their Sensitivity of Ventilator Associated Pneumonia in an Intensive Care Unit of a Ter-tiary Care Hospital in Dhaka - Kashfi, Tasmia; Ahsan, ASM Areef; Sultana, Rozina (Bangladesh Critical Care Journal, 2022)
Background: ICU admission imposes great risk of nosocomial infections on the patients due to various invasive interventions. Patients treated in these units receive invasive procedures such as endotracheal intubation and mechanical ventilation which predispose to a nosocomial pneumonia of a special entity named as ‘Ventilator Associated Pneumonia’. Almost half of all the cases of hospital acquired pneumonia are due to VAP and about half of all antibiotics administration in ICU are for treatment of Ventilator Associated Pneumonia. Objectives: objective of the current study was to study the local microbiological profile of ventilator associated pneumonia and their sensitivity pattern in the Critical Care department of BIRDEM general hospital. Design: Cross-sectional study. Setting: ICU of an academic tertiary care hospital in the period of July 2017 to June 2018. Methods: All consecutive patients who were intubated and mechanically ventilated for a period of at least 48 hours within the study period were evaluated for the selection criteria of the study. The included study participants were followed up daily for signs of development of VAP. Once VAP was suspected pertinent investigations were sent to confirm the diagnosis. Tracheal aspirate was collected using conventional specimen trap and aseptic endotracheal suctioning technique and sent for Gram staining and culture and sensitivity testing. Results: In this study total 92 patients out of 625 intubated patients during the study period after fulfilling the inclusion criteria were selected as study participants. 35 participants out of 92developed VAP. Only 1 (2.9 %) patient did not yield any microbial growth in the tracheal aspirate sample and 34 (97.2 %) participants had growth of organisms in their tracheal aspirate samples. Total growths of 45 organisms were found in respiratory secretions of 34 VAP patients. The commonest organism was Acinetobacter which was grown in 21 (46.7%) samples followed by Pseudomonas in 10 (22.2%) samples; Klebsiella in 8 (17.8%) samples; Staphylococcus aureus in 3 (6.7%) samples; Candida in 2 (4.4%) and Enterococcus in 1 sample (2.2%). Most of the bacteria grown in the tracheal aspirates of VAP positive participants were sensitive to less than three antibiotic classes. Conclusion: Multidrug resistant organisms are mostly responsible for both early and late onset VAP in ICU. Bangladesh Crit Care J September 2022; 10(2): 122-126